2009
DOI: 10.1038/icb.2009.90
|View full text |Cite
|
Sign up to set email alerts
|

Cross, but not direct, presentation of cell‐associated virus antigens by spleen macrophages is influenced by their differentiation state

Abstract: The initiation of T-cell immune responses requires professional antigen-presenting cells. Emerging data point towards an important role for macrophages (M/) in the priming of naïve T cells. In this study we analyzed the efficiency and the mechanisms by which M/ derived from spleen (Sp-M/) or bone marrow (BM-M/) present Lymphocytic choriomeningitis virus (LCMV) antigens to epitope-specific T cells. We demonstrate that because of phagosomal maturation, Sp-M/ downregulate their ability to cross-present cell-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…It is likely that the majority of the CD11c À populations are Mø that were reported to cross-present antigens in a comparable manner to DC [27,28]. Interestingly, NP396 was the best epitope to be cross-presented by the CD11c 1 cell, which confirms our observation in vitro.…”
Section: Discussionsupporting
confidence: 87%
“…It is likely that the majority of the CD11c À populations are Mø that were reported to cross-present antigens in a comparable manner to DC [27,28]. Interestingly, NP396 was the best epitope to be cross-presented by the CD11c 1 cell, which confirms our observation in vitro.…”
Section: Discussionsupporting
confidence: 87%
“…Viral infection induces changes of cell surface molecules related to cell death, and macrophages can recognize these changes and engulf the affected cells. It has been reported that macrophages perform efferocytosis of cells infected with the influenza (Fujimoto et al, 2000; Hashimoto et al, 2007; Shiratsuchi et al, 2000; Watanabe et al, 2005, 2002, 2004; Mukherjee et al, 2017), papilloma (Hermetet et al, 2016), and Drosophila C viruses (Nainu et al, 2015; Nonaka et al, 2017), as well as Lymphocytic choriomeningitis virus (LCMV) (Alatery et al, 2010), and Human Immunodeficiency Virus Type 1 (HIV-1) (Akbar et al, 1994). …”
Section: Introductionmentioning
confidence: 99%
“…It is possible that TLR-L influences cross-presentation through antigen uptake as well as by altering other parameters, such as phagosomal pH through NOX2 activation (3,35). Increased NOX2 activity could exacerbate antigen degradation, which in turn reduces the amount of antigen available from cross-presentation (1,27).…”
Section: Discussionmentioning
confidence: 99%
“…NP396-specific CTLs were generated as previously described (1,5). Briefly, mice were injected with 200 PFU LCMV-WE intravenously (i.v.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation